# The Difference of Two Squares Revision and worksheets

GCSE 6 - 7AQAEdexcelOCRWJECHigherEdexcel 2022WJEC 2022

## The Difference of Two Squares

The difference of two squares is precisely that. One squared thing subtracted from another squared thing. This means they are straightforward to factorise. Make sure your happy with the following topics before continuing.

## Difference of Two Squares Formula

The trick to factorising the difference of two squares is to use the formula,

$\textcolor{blue}{a^2 -b^2 = (a+b)(a-b)}$

This can be used in either direction to factorise or expand such expressions quickly. To show that this works, we will expand the two brackets of the general formula.

\begin{aligned} \textcolor{blue}{(a+b)(a-b)} & =\textcolor{black}{ a^2 +\cancel{ab} - \cancel{ab} -b^2 }\\ &= \textcolor{blue}{a^2 -b^2} \end{aligned}

The negative sign arises as you are multiplying a negative by a positive thus the result is negative. As you can see the two ‘cross terms’ involving both $a$ and $b$ cancel, so we are left with just the square terms.

Level 6-7 GCSE

## Example 1: Factorising a Simple Quadratic

Factorise $x^2 - 9$.

[2 marks]

Identifying that this is a difference of two squares, $a$ and $b$ are simply the square roots of $x^2$ and $9$ respectively. Hence $a=\sqrt{x^2}=x$ and $b=\sqrt{9}=3$. So the factorisation is,

$(x+3)(x-3)$

Level 6-7 GCSE

## Example 2: Removing a Common Factor

Factorise $4x^2 - 100y^2$.

[3 marks]

This is still a question involving the difference of two squares however a factor of $4$ has to be taken out first,

$4x^2 - 100y^2 = 4(x^2-25y^2)$

Now we can find $a$ and $b$ by taking the square roots of $x^2$ and $25y^2$ respectively. Hence $a=\sqrt{x^2}=x$ and $b=\sqrt{25y^2}=5y$. So the factorisation is,

$4(x+5y)(x-5y)$

Level 6-7 GCSE

## Example 3: Factorising a Quadratic involving Surds

Factorise $y^2 - 7$.

[2 marks]

In some cases the values we find for $a$ or $b$ will be a surd (non-terminating square root) . In this instance $a=\sqrt{y^2}=y$ and $b=\sqrt{7}=\sqrt{7}$. So the factorisation is,

$(y+\sqrt{7})(y-\sqrt{7})$

Level 6-7 GCSE

## Example Questions

Identifying that both of the coefficients of each term are square numbers, then the square roots are $a=\sqrt{9x^2}=3x$ and $b=\sqrt{49y^2}=7y$. So the factorisation is,

$(3x+7y)(3x-7y)$

Here we can remove a factor of $2$ first so,

$2x^2 - 8 =2(x^2 - 4)$

Thus the factorisation is,

$2(x + 2)(x - 2)$

This is a difference of two squares so we can apply the formula the same way,

$99^2-98^2=(99+98)(99-98) = (197)(1)=197$

## Related Topics

Level 4-5Level 6-7

## You May Also Like...

### GCSE Maths Revision Cards

Revise for your GCSE maths exam using the most comprehensive maths revision cards available. These GCSE Maths revision cards are relevant for all major exam boards including AQA, OCR, Edexcel and WJEC.

£8.99

### GCSE Maths Revision Guide

The MME GCSE maths revision guide covers the entire GCSE maths course with easy to understand examples, explanations and plenty of exam style questions. We also provide a separate answer book to make checking your answers easier!

From: £14.99

### Transition Maths Cards

The transition maths cards are a perfect way to cover the higher level topics from GCSE whilst being introduced to new A level maths topics to help you prepare for year 12. Your ideal guide to getting started with A level maths!

£8.99